2012
DOI: 10.1080/09540121.2011.630341
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors related to HIV-risk behavior: A comparison between HIV-positive and HIV-negative young men who have sex with men

Abstract: The objective of this study was to assess and compare the prevalence of high-risk sexual behaviors among young HIV-negative (n=8064) and HIV-positive (n=171) men who have sex with men (MSM) on predictors of unprotected anal intercourse (UAI). Using venue-based time-space sampling, 8235 MSM aged 15-25 were anonymously surveyed as a part of the Community Intervention Trial for Youth (CITY). The Project was conducted in 13 communities across the USA from 1999 to 2002. Forty percent of HIV-positive men and 34% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…The National HIV Behavioral Surveillance System (NHBS) [3] and research studies [4-7] have relied, in part, on venue-based, time-space sampling (VBTS) [8] for the recruitment of MSM populations. In VBTS, after a period of formative research, venues (eg, bars, dance-clubs) attended by MSM are identified by health department staff members and calendars marking the days and times of venue attendance are created.…”
Section: Introductionmentioning
confidence: 99%
“…The National HIV Behavioral Surveillance System (NHBS) [3] and research studies [4-7] have relied, in part, on venue-based, time-space sampling (VBTS) [8] for the recruitment of MSM populations. In VBTS, after a period of formative research, venues (eg, bars, dance-clubs) attended by MSM are identified by health department staff members and calendars marking the days and times of venue attendance are created.…”
Section: Introductionmentioning
confidence: 99%
“…HIV prevalence estimates computed using pooled data from seven Asian countries (Thailand, Vietnam, Cambodia, China, Indonesia, India and Nepal), found that MSM are 19 times more likely to get infected than other men of reproductive age [1]. MSM are particularly vulnerable to HIV because of their wide range of HIV-related risk behaviours including high number of sexual partners, bisexual behaviour, inconsistent condom use, substance use, transactional sex, and low levels of awareness on HIV and sexually transmitted infections (STIs) [6,7]. Studies conducted among MSM in low and middle-income countries have demonstrated that HIV risks are associated with a variety of sexual partnerships and sexual practices [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…45,63,64 HIV-positive and HIV-negative men differ on a number of psychosocial, behavioural and sociodemographic variables. [65][66][67] Engagement in HIV risk-related behaviour differs according to HIV status on a fundamental level: for the HIV-positive person risks are focused on potentially infecting another person (i.e. relatively little impact to self), and for the HIV-negative person risks are focused on the potential for them to become infected (i.e.…”
Section: Background and Rationalementioning
confidence: 99%